Telitromicine. A new therapeutic option from macrolides to ketolides. - Pedro Miguel Milián Vázquez; Maira Quirós Enríquez; Arlette Linares Borges (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2004)
-